Analysis Of Students ' Understanding Of Mathematical Concepts In Class Viii Function Material Smp Negeri Satu Atap Tanjung Balai T.P 2021/2022 - Thota Murni Gultom; Hardi Tambunan (CV. AFDIFAL MAJU BERKAH, 2022)
This study aims to determine the understanding of mathematical concepts of students in the material function in Class VIII SMP Negeri Satu Atap Tanjung Balai T.P 2021/2022. This study is a quantitative descriptive research. The population in this study were all students of Class VIII SMP Negeri Satu Atap Tanjung Balai consisting of two classes, namely VIII-1 and VIII-2 as many as 64 people, and the sample in this study was Class VIII-1 as many as 32 people taken by cluster random sampling technique. The instrument used in this study using a test instrument description form. Based on the analysis of data obtained shows that in the interval X > 93 there is 1 person with a percentage of 3% and very high ability category, interval 82 < X < 93 there are 6 people with a percentage of 19% with high ability category, interval 70 < X < 82 there are 18 people with a percentage of 56% with medium ability category, interval 59 < X < 70 there are 5 people with a percentage of 16% with low category, interval X < 59 There are 2 people with a percentage of 6% with very low category. So, the ability of students in understanding the concept of material function Class VIII SMP Negeri Satu Atap Tanjung Balai T.P 2021/2022 belongs to the medium category in the interval 70 < X < 82 as many as 18 people with a percentage of 56%..